New experimental tools for bioassays with whitefly in laboratory - Fanela, Thiago Luis Martins; Baldin, Edson Luis Lopez; Fujihara, Ricardo Toshio (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to develop an experimental kit for assessments of repellency, deterrence for oviposition, and insecticidal activity on adults of the whitefly Bemisia tabaci biotype B. The kit, which consisted of arenas and nebulizer, was effective for conducting bioassays, and the application of aqueous extracts by inhaler was adequate. The techniques are simple, cheap, and may contribute to research on this insect.